Healthy Organizations: Toward a Diagnostic Method Ii - Tarride-Fernandez, M (Emerald Group Publishing Ltd., 2014)
Purpose: To contribute to the search for new viewpoints that will enrich the understanding of the complex organizational phenomenon, in particular by contributing to the development of a method that allows qualifying, in the fullest possible way, whether an organization can be said to be healthy. So the objective of this work has been to experiment with the diagnostic method of the organizational health situation - proposed in a previous paper published in this journal - through applications that allowed backfeeding it and offering a new improved version of it. The paper aims to discuss these issues. Design/methodology/approach: The present work takes up the challenge of advancing in the development of the method of determining the health condition of an organization, revising the general homomorphism as well as the information that will be considered, its sources, the way of obtaining it, and the way of making the synthesis that will allow issuing the final overall judgement of healthy or not of the organization that is being studied. To that end, recourse is made to the experience obtained from eight applications made to different kinds of small organizations in the city of Santiago, Chile, from 2008 to 2012. Findings: The human-being/organization homomorphism was reformulated, going from eight component systems of the human body to 13, by reformulating some and incorporating others. Although a set of indicators may be used in different kinds of organizations, each one of them also presents a specificity that makes it highly complicated to make comparisons; the health situation of an organization is related only to itself. Consequently, the set of indicators that are selected to determine the health condition of an organization depends on itself. Not all the variables, systems and dimensions have the same weight for those interested in the overall health judgement to be issued, so this task of searching for the weights becomes a key aspect of the method: what was found to be most advisable was to set up a group of experts composed of key informants belonging to the organization itself and of external analysts. The symptoms - perceptions of the key informants - must be transformed into signs that allow objectifying the judgement of healthy or not of an organization. Originality/value: The work contributes new elements that enrich the method for diagnosing organizational health proposed earlier, starting from the homomorphism established between the way in which allopathic physicians study their patients and the way the analyst operates with an organization. © Emerald Group Publishing Limited.